INVESTMENT RISK, INVESTMENT OPPORTUNITY SET DAN RETURN SAHAM - Nuke Yusma; Holiawati Holiawati (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2019)
The purpose of this study was to determine the effect of investment risk and Investment Opportunity Set on stock returns in Manufacturing Companies in the Industrial Sector of Consumer Goods Listed on the Indonesia Stock Exchange 2013-2017.  This type of research is quantitative associative, namely to determine the relationship of two or more variables in this study using quantitative data or data in the form of numerical or numeric. The type of data used is secondary data, namely data obtained from IDX and PT Pefindo. The sampling technique was using purposive sampling technique with certain criteria, so that 58 samples were obtained. The method of data analysis uses multiple regression analysis and is accompanied by a statistical descriptive test, classic assumption test, hypothesis test (t test and F test). The results of the study state that partially investment risk proxied by market risk (beta) has no effect and is not significant on stock returns and Investment The Opportunity Set proxied with MBVA has an effect and significant on stock returns. Simultaneously investment risk and Investment Opportunity Set have an effect and significant to stock returns